MENUNGGU KINERJA KOMNAS DIFABEL BERMITRA DENGAN KEPANDUAN DALAM MENGEVALUASI FASILITAS PASAR TRADISIONAL - Moh. Rosyid (Wacana Publik, 2021)
The purpose of writing is give feedback for National Commition of Disability for optimal to carry out the taskto evaluation of Law No. 8 of 2016 on People with Disabilities in relation with market traditional to facilitation from disability. Data form observation, literature and were analyzed in descriptive qualitative method. The market as a public facility (public agency) is obliged to provide easy access to facilities and infrastructure for the public and persons with disabilities. The law authorizes the government to establish an independent institution (National Commission for Disabilities) in order to evaluate the organizers of public facilities in compliance with the Law on Disabilities. However, due to the limited number of members of the National Commission for Disabilities, its performance needs to be in partnership with Scouting in educational institutions. Scouting carries the spirit as a cadre institution for generations who are helpful, honest, caring for others and are responsible for being an ideal partner.